Hypoxic effects on the mitochondrial content and functions of the placenta in fetal growth restriction. (October 2021) - Xu, Yue-Ying; Liu, Yuan; Cui, Ling; Wu, Wei-Bin; Quinn, Martin John; Menon, Ramkumar; Zhang, Hui-Juan
Abstract: Introduction: In this study we examined the hypothesis that a hypoxic intrauterine environment causes mitochondrial dysfunction of trophoblasts in fetal growth restriction (FGR). Methods: The mtDNA content, mRNA levels of mitochondrial encoded genes (ND6, COX I), mitochondrial membrane proteins (COX I, COX IV and VDAC), HIF-1α and BINP3 (mitophagy receptor) protein levels were examined in FGR placentas and normal placentas. The mitochondrial function (ATP production and mitochondrial membrane potential-ΔΨm) and above related proteins were further examined in hypoxic HTR-8/SVneo cells induced by cobalt chloride (CoCl2). Mitophagy and its regulating mechanism under hypoxia in FGR was also investigated. Results: Compared with normal controls, both FGR placentas and CoCl2-treated trophoblast cells demonstrated statistically lower mtDNA content, reduced mRNAs of mitochondrial encoding genes, and decreased mitochondrial membrane proteins, accompanied by increased HIF-1α. Mitochondrial functions were impaired as demonstrated by decreased ATP production, and, reduced ΔΨm in CoCl2-treated cells. Meanwhile, mitophagy was markedly enhanced as indicated by increased LC3 fluorescent puncta in mitochondria of hypoxic trophoblastic cells. The upregulated BINP3 expression was demonstrated in FGR placentas as well as in hypoxic trophoblastic cells. Discussion: We demonstrated that hypoxic conditions lead to impaired mitochondrial function in trophoblasts in FGR. Reduced mtDNA may be associated with enhanced mitophagy via activating HIF-1α/BINP3 signalling pathway, that may, in turn, affect nutrition and energy transfer to the growth-restricted fetus. Highlights: Under hypoxic conditions, mitochondria were impaired at mtDNA, mRNA and protein levels in FGR placentas. Trophoblastic cells, in an in vitro hypoxic model, showed reduced ATP and ΔΨm with enhanced mitophagy. Upregulated mitophagy in hypoxia may contribute to reduced mtDNA content via activating HIF-1α/BINP3 signal pathway.